Improving the Electrical Conductivity of the Composite Comprising Bismuth Oxide, Activated Carbon, and Graphite for Use as a Battery Anode - Yayuk Astuti; Faradina Azahra Zaqia; Aulia Zahra Ekaningsih; Gunawan Gunawan; Adi Darmawan (Universitas Gadjah Mada, 2023)
This research is concerned with the synthesis and characterization of a composite material that may be used as a battery electrode. Bismuth oxide (Bi2O3) was synthesized from Bi(NO3)3·5H2O, Na2SO4, and NaOH mixed with commercial activated carbon and graphite. The composite formation process was carried out using the hydrothermal method at 110 °C for 5 h. The characterization data indicated the composites produced contained Bi2O3 with a monoclinic crystal system, and Bi2O3 particles were evenly distributed in the composite. The composites were characterized to be mesoporous, with the electrical conductivity reaching 10−1 S m−1. The development of this composite material has potential applications in the field of energy storage, particularly in the development of battery anode.